Potensi Ekowisata Dan Strategi Pengembangan Tahura Nipa-nipa, Kota Kendari, Sulawesi Tenggara - Alamsyah Flamin; Asnaryati (Jurnal Penelitian Kehutanan Wallacea, 2013)
This study aims to determine the potency and nature tourism development strategy in the region of Tahura Nipa-Nipa. The research was conducted at the Regions Tahura Nipa-Nipa Kendari City in Southeast Sulawesi Province in 2010. The methodology of this study is to use surveys and The results showed that the potential attraction of Nipa-Nipa Tahura Region consists of potential flora-fauna and natural scenery. Potential flora consists of various plant species habitus trees, including the type of wood resin, Bintangur, Eha, including species of palm Nongella sp, and rattan. The endemic fauna are anoa, deer, Sulawesi black monkey, wild boar, species such as reptiles lizard, python. Some species of bird such as the pigeon forest, cuckoo. The potential natural beauty consists of objects such as Lahundape waterfall and a campground. Alternative strategies for developing ecotourism in the Nipa-Nipa Tahura is SO strategy to develop an optimal potential of flora, fauna, natural scenery and indigenous communities in package by using the support from the government and local communities. While WO strategies take advantage of the support of the community and the local government to improve the quality of tourism, particularly in the sights of Waterfall Lahundape.